2017
DOI: 10.15330/ms.48.1.3-13
|View full text |Cite
|
Sign up to set email alerts
|

On the automorphism group of the superextension of a semigroup

Abstract: A family A of non-empty subsets of a set X is called an upfamily if for each set A ∈ A any set B ⊃ A belongs to A. An upfamily L of subsets of X is said to be linked if A ∩ B ̸ = ∅ for all A, B ∈ L. A linked upfamily M of subsets of X is maximal linked if M coincides with each linked upfamily L on X that contains M. The superextension λ(X) consists of all maximal linked upfamilies on X. Any associative binary operation * : X ×X → X can be extended to an associative binary operation * : λ(X) × λ(X) → λ(X). In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Difference bases and difference characteristics in dihedral and Abelian groups were investigated in [3,4]. Difference bases have applications in the study of structure of superextensions of groups, see [1,5,9].…”
Section: Theorem 4 ([13]mentioning
confidence: 99%
“…Difference bases and difference characteristics in dihedral and Abelian groups were investigated in [3,4]. Difference bases have applications in the study of structure of superextensions of groups, see [1,5,9].…”
Section: Theorem 4 ([13]mentioning
confidence: 99%
“…In this paper, we investigate the automorphism groups of the extensions N k (S) of a semigroup S. The thorough study of various extensions of semigroups was started in [13] and continued in [1][2][3][4][5][6][7][8][9][10][14][15][16][17][18][19]. The largest among these extensions is the semigroup υ(S) of all upfamilies on S. A family A of non-empty subsets of a set X is called an upfamily if for each set A ∈ A any subset B ⊃ A of X belongs to A.…”
Section: Introductionmentioning
confidence: 99%
“…The thorough study of automorphism groups of superextensions of semigroups was started in [19] and continued in [9]. In [19] it was shown that each automorphism of a semigroup S can be extended to an automorphism of its superextension λ(S) and the automorphism group Aut (λ(S)) of the superextension of a semigroup S contains a subgroup, isomorphic to the automorphism group Aut (S) of S. Also the automorphism groups of superextensions of null semigroups, almost null semigroups, right zero semigroups, left zero semigroups and all three-element semigroups were described. In [9] we studied the automorphism groups of superextensions of groups and described the automorphism groups Aut (λ(G)) of the superextensions of all groups G of cardinality |G| ≤ 5.…”
Section: Introductionmentioning
confidence: 99%